2016
DOI: 10.1021/acs.iecr.6b02468
|View full text |Cite
|
Sign up to set email alerts
|

Levulinic Acid Production from Starch Using Microwave and Oil Bath Heating: A Kinetic Modeling Approach

Abstract: This work examines the role played by starch composition and heating media in the synthesis of the promising biorefinery chemical levulinic acid (LA). Three corn starches with different amylose/amylopectin ratios were converted to LA using both microwave and conventional oil bath heating. The results obtained for the different reaction temperatures and times were used to calculate kinetic parameters using a multireaction model. It was observed that the long preheating and cooling times employed in microwave he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Dumont [22] with 55% LA yield from corn starch at 180ºC in 15 min, Jeong [18] with 25% LA yield from glucosamine at 188ºC in 49 min and Shen et al [23] with 39% LA yield from cellulose in 2 h. It should be noted that in the abovementioned studies the starting materials were pure carbohydrates where as in this study biomass was used as received without prior separation of carbohydrates. Thus the LA yields achieved in this study are highly comparable with the yields reported in literature.…”
Section: The Effect Of Lewis Acid Catalyst and The Reaction Time On Lmentioning
confidence: 92%
“…Dumont [22] with 55% LA yield from corn starch at 180ºC in 15 min, Jeong [18] with 25% LA yield from glucosamine at 188ºC in 49 min and Shen et al [23] with 39% LA yield from cellulose in 2 h. It should be noted that in the abovementioned studies the starting materials were pure carbohydrates where as in this study biomass was used as received without prior separation of carbohydrates. Thus the LA yields achieved in this study are highly comparable with the yields reported in literature.…”
Section: The Effect Of Lewis Acid Catalyst and The Reaction Time On Lmentioning
confidence: 92%
“…Table 1 shows the estimated kinetic parameters of levulinic acid production using various substrates and acid catalysts under different operating conditions. In most of the cases cited in this table, the kinetics of each reaction was described by two coefficients: the preexponential factor (A i ) and activation energy (E Ai ), assuming a first order reaction (Shen and Wyman 2012;Weingarten et al 2012;Rivas et al 2014;Fachri et al 2015;Ren et al 2015;Mukherjee and Dumont 2016;Tan-Soetedjo et al 2017). In addition, some studies (Chang et al 2006;Lenihan et al 2011), despite having established that the order of reaction (m i ) differs from 1, do not describe the kinetics of levulinic acid production under this consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The varieties have different starch granules’ mean diameters ( Table 1 ). Potato starch was converted to levulinic acid according to the procedure described in [ 21 ]. The reaction was repeated in duplicate with the starch of each potato variety.…”
Section: Methodsmentioning
confidence: 99%